Anxiety and Defense Mechanism of Joy Newsome in Room Movie - Putra, Harli Aprian; Astuti, Anjar Dwi; Ariani, Setya (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
The first purpose of this study was to determine the type of anxiety experienced by Joy in the Room movie (2015). Besides, this study also aimed to determine the type of defense mechanism Joy Newsome used to overcome her anxiety. This study was qualitative research because it focused on analyzing the psychological aspect of a character in a movie. Accordingly, the approach used here was the psychological approach. In this study, the researcher used Freud's theory about anxiety and defense mechanisms. Based on the results of the study, it was found that Joy Newsome experienced moral anxiety and realistic anxiety. To overcome her anxiety, Joy used several types of defense mechanisms. Those defense mechanisms are repression, reaction formation, denial, displacement, regression projection and fantasy.